2015
DOI: 10.1016/j.jvs.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Time and flow-dependent changes in the p27 gene network drive maladaptive vascular remodeling

Abstract: Objectives Although clinical studies have identified that a single nucleotide polymorphism in the p27kip1 gene is associated with success or failure following vein bypass grafting, the underlying mechanisms for this difference are not well defined. Using a high-throughput approach in a flow-dependent vein graft model, we explored the differences in p27kip1 -related genes that drive the enhanced hyperplastic response under low flow conditions. Methods Bilateral rabbit carotid artery interposition grafts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Anesthesia was maintained with endotracheal intubation and continuous isoflurane inhalant anesthesia (2% during painful stimuli, and 1% at latent periods). Vein bypass grafts were constructed with an anastomotic cuff technique as previously as described [ 11 , 12 ]. Bilateral carotid artery interposition grafting with jugular vein and unilateral distal carotid artery branch ligation were performed to create two distinct flow states.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anesthesia was maintained with endotracheal intubation and continuous isoflurane inhalant anesthesia (2% during painful stimuli, and 1% at latent periods). Vein bypass grafts were constructed with an anastomotic cuff technique as previously as described [ 11 , 12 ]. Bilateral carotid artery interposition grafting with jugular vein and unilateral distal carotid artery branch ligation were performed to create two distinct flow states.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral carotid artery interposition grafting with jugular vein and unilateral distal carotid artery branch ligation were performed to create two distinct flow states. Briefly, differential flow states between the right and left vein grafts were accomplished by ligation of the internal carotid artery and three of the four primary branches of the external carotid artery, resulting in an immediate six fold difference in mean shear stress [ 11 , 12 ]. Routine daily postoperative care and analgesia was provided, including daily neurologic assessment up to day 5 post surgery to identify any or all of head tilt, ear droop, or extremity weakness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms behind how genes affect biological systems are currently being studied in vascular biology. For example, clinical studies have shown that a “single nucleotide in the p27 kip1 gene” affects the likelihood of success versus failure following vein bypass grafting 35 . The mechanical response of the graft to the high arterial pressure – or of medial-layer smooth muscle to loading in the case of arterial remodeling – should also be considered, so it is imperative that one understands the mechanical properties of the tissue at the continuum scale and also at the microscopic scale.…”
Section: Vascular Biology Imaging and Biomechanicsmentioning
confidence: 99%